2021
DOI: 10.1136/bmjopen-2021-050519
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of contact tracing apps for SARS-CoV-2: a rapid systematic review

Abstract: ObjectiveTo systematically review evidence on effectiveness of contact tracing apps (CTAs) for SARS-CoV-2 on epidemiological and clinical outcomes.DesignRapid systematic review.Data sourcesEMBASE (OVID), MEDLINE (PubMed), BioRxiv and MedRxiv were searched up to 28 October 2020.Study selectionStudies, both empirical and model-based, assessing effect of CTAs for SARS-CoV-2 on reproduction number (R), total number of infections, hospitalisation rate, mortality rate, and other epidemiologically and clinically rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 28 publications
0
35
2
1
Order By: Relevance
“…The apps inform users about contact with positive (infected) cases, suggest adequate preventive and mitigation measures, and allow governmental institutions to define containment or hotspot zones (Kahnbach et al, 2021). Previous studies examined barriers and facilitators of adopting tracing app use and showed that they are effective in reducing infection rates (e.g., Jenniskens et al, 2021;Kahnbach et al, 2021;Kolasa et al, 2021). However, tracing apps often do not provide sufficient information about personal data breaches, which might increase privacy concerns and subsequently, reduce use intentions (Jenniskens et al, 2021).…”
Section: Literature Review Of Information Privacy Measures In Mobile ...mentioning
confidence: 99%
“…The apps inform users about contact with positive (infected) cases, suggest adequate preventive and mitigation measures, and allow governmental institutions to define containment or hotspot zones (Kahnbach et al, 2021). Previous studies examined barriers and facilitators of adopting tracing app use and showed that they are effective in reducing infection rates (e.g., Jenniskens et al, 2021;Kahnbach et al, 2021;Kolasa et al, 2021). However, tracing apps often do not provide sufficient information about personal data breaches, which might increase privacy concerns and subsequently, reduce use intentions (Jenniskens et al, 2021).…”
Section: Literature Review Of Information Privacy Measures In Mobile ...mentioning
confidence: 99%
“…Visualization ( [10] ), machine learning ( [11] , [12] , [13] ) and statistical modeling ( [14] ), robotics ( [11] ), and contact tracing ( [15] ) has been the major focus of the engineers in the recent past that have helped slow down the spread of COVID-19 and reduce the moveability. Geostatistical modeling helps better understanding the disease trend and facilitates the informed decision-making process ( [16] ).…”
Section: Motivation and Significancementioning
confidence: 99%
“…Despite implementation in many countries, little empirical evidence exists about the effectiveness of digital tracing applications. (13, 14) While two recent evaluations from the United Kingdom and Switzerland suggest that systems based on the decentralised approach may be able to provide some benefits to a country’s COVID-19 response under certain conditions, (15, 16) no evidence exists to date about the population-level effectiveness of decentralized digital contact tracing applications. Considering the substantial investments to develop, promote and maintain these systems, it is important to establish how well they work, and what their added value within the existing contact tracing system is.…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10)(11)(12) Despite implementation in many countries, little empirical evidence exists about the effectiveness of digital tracing applications. (13,14) While two recent evaluations from the United Kingdom and Switzerland suggest that systems based on the decentralised approach may be able to provide some benefits to a country's COVID-19 response under certain conditions, (15,16) no evidence exists to date about the population-level effectiveness of decentralized digital contact tracing applications.Considering the substantial investments to develop, promote and maintain these systems, it is important to establish how well they work, and what their added value within the existing contact tracing system is. (17) Therefore, we assessed the effectiveness and usefulness of the COVIDSafe app, Australia's national smartphone-based proximity tracing application.…”
mentioning
confidence: 99%